(untitled) (Journal of Pharma Insights and Research, 2024)
Achalasia cardia is an uncommon esophageal motility disorder characterized by the impaired relaxation of the lower esophageal sphincter (LES) and the absence of peristaltic contractions in the esophageal body. This report presents a case of a 42-year-old woman with a prolonged history of dysphagia and regurgitation of solids and liquids. The patient’s clinical history included a 10-year history of neck swelling, hypothyroidism, and diabetes mellitus. Physical examination and laboratory investigations revealed normal findings, except for elevated blood glucose, thyroid hormone levels, and thyroid-stimulating hormone (TSH) levels. An esophagogram showed proximal dilation of the distal esophagus with a contrast fluid level, and endoscopy revealed a tight LES, which was difficult to pass through. Based on these findings, the diagnosis of achalasia cardia was established. Initial medical management with nitrates and proton pump inhibitors did not provide significant improvement. Subsequently, the patient underwent laparoscopic Heller’s myotomy with fundoplication, which successfully resolved her dysphagia symptoms. This case report highlights the diagnostic challenges and the importance of a multidisciplinary approach in managing achalasia cardia. It emphasizes the role of surgical interventions, such as Heller’s myotomy with fundoplication, in alleviating symptoms and restoring esophageal function when conservative medical management fails